Attenuation and molecular characterization of fowl adenovirus 8b propagated in a bioreactor and its immunogenicity, efficacy, and virus shedding in broiler chickens - Ugwu, Chidozie Clifford; Bejo, Mohd Hair; Mat Isa, Nurulfiza; Omar, Abdul R; Ideris, Aini (Veterinary World, 2024)
Background and Aim: Live-attenuated vaccines are the most successful type of vaccine and could be useful in controlling fowl adenovirus (FAdV) 8b infection. This study aimed to attenuate, molecularly characterize, and determine the immunogenicity, efficacy, and challenge virus shedding in broiler chickens. Materials and Methods: The FAdV 8b isolate (UPM08136) was passaged onto chicken embryo liver (CEL) cells until attenuation. We sequenced and analyzed the hexon and fiber genes of the passage isolates. The attenuated bioreactor-passage isolate was inoculated into 1-day-old broiler chickens with (attenuated and inactivated) and without booster groups and challenged. Body weight (BW), liver weight (LW), liver: body weight ratio (LBR), FAdV antibody titers, T-lymphocyte subpopulation in the liver, spleen, and thymus, and challenge virus load and shedding were measured. Results: Typical cytopathic effects with novel genetic changes on CEL cells were observed. The uninoculated control-challenged (UCC) group had significantly lower BW and higher LW and LBR than the inoculated groups. A significantly higher FAdV antibody titer was observed in the challenged non-booster and attenuated booster groups than in the UCC group. T cells in the spleen and thymus of the liver of inoculated chickens were higher than uninoculated control group levels at all-time points and at different times. A significantly higher FAdV challenge virus load was observed in the liver and shedding in the cloaca of UCC chickens than in non-booster chickens. Conclusion: The FAdV 8b isolate was successfully attenuated, safe, and immunogenic. It reduces virus shedding and is effective and recommended as a vaccine against FAdV infection in broiler chickens.